The future of US farm policy - Smith, Vincent H.; Glauber, Joseph W. (Wiley, 2019)
The farm bill is the primary legislative vehicle for federal food and agricultural policies in the United States that is renewed roughly once every five years. Most current farm bill subsidy and other domestic support programmes for agriculture have their origins in legislation introduced in the 1930s to alleviate poverty among farm households during the Great Depression. Although US farm households have enjoyed higher incomes and wealth than the average US family for many years, legislation to support agricultural commodity prices and to increase farm incomes has persisted. A new farm bill offers the US Congress an opportunity to reform agricultural subsidy policies. But if recent history is a guide, what will emerge is likely to resemble much of what was in the 2014 bill. As was the case with that bill, maintaining the status quo will represent a missed opportunity to cut farm subsidies and make agricultural programmes more market oriented, and be unlikely to improve trade relations for the United States in the context of its commitments under current World Trade Organization agreements. In many ways, agricultural policy in the United States seems to be firmly marching back to the past rather than looking to the future.